Attentional Focus and Grip Width Influences on Bench Press Resistance Training. Issue 2 (April 2018) - Calatayud, Joaquin; Vinstrup, Jonas; Jakobsen, Markus D.; Sundstrup, Emil; Carlos Colado, Juan; Andersen, Lars L.
This study evaluated the influence of different attentional foci for varied grip widths in the bench press. Eighteen resistance-trained men were familiarized with the procedure and performed a one-repetition maximum (1RM) test during Session 1. In Session 2, they used three different standardized grip widths (100%, 150%, and 200% of biacromial width distance) in random order at 50% of 1RM while also engaged in three different attention focus conditions (external focus on the bench press, internal focus on pectoralis major muscles, and internal focus on triceps brachii muscles). Surface electromyography (EMG) signals were recorded from the triceps brachii and pectoralis major, and peak EMG of the filtered signals were normalized to maximum EMG of each muscle. Both grip width and focus influenced the muscle activity level, but there were no significant interactions between these variables. Exploratory analyses suggested that an internal focus may slightly (4%–6%) increase pectoralis major activity at wider grip widths and triceps brachii activity at narrower grip widths, but this should be confirmed or rejected in a study with a larger sample size or through a meta-analysis of research to date.